Carbon isotope‐constrained seasonality of carbonaceous aerosol sources from an urban location (Kanpur) in the Indo‐Gangetic Plain. Issue 9 (2nd May 2017) - Bikkina, Srinivas; Andersson, August; Ram, Kirpa; Sarin, M. M.; Sheesley, Rebecca J.; Kirillova, Elena N.; Rengarajan, R.; Sudheer, A. K.; Gustafsson, Örjan
Abstract: The Indo‐Gangetic Plain (IGP) in northern India, Pakistan, and Bangladesh is a major source of carbonaceous aerosols in South Asia. However, poorly constrained seasonality of their sources over the IGP leads to large uncertainty in climate and health effects. Here we present a first data set for year‐round radiocarbon (Δ 14 C) and stable carbon (δ 13 C)‐based source apportionment of total carbon (TC) in ambient PM10 ( n = 17) collected from an urban site (Kanpur: 26.5°N, 80.3°E) in the IGP during January 2007 to January 2008. The year‐round 14 C‐based fraction biomass ( f bio‐TC ) estimate at Kanpur averages ~77 ± 7% and emphasizes an impact of biomass burning emissions (BBEs). The highest f bio‐TC (%) is observed in fall season (October–November, 85 ± 6%) followed by winter (December–February, 80 ± 4%) and spring (March–May, 75 ± 8%), while lowest values are found in summer (June–September, 69 ± 2%). Since biomass/coal combustion and vehicular emissions mostly contribute to carbonaceous aerosols over the IGP, we predict δ 13 CTC (δ 13 Cpred ) over Kanpur using known δ 13 C source signatures and the measured Δ 14 C value of each sample. The seasonal variability of δ 13 Cobs  − δ 13 Cpred versus Δ 14 CTC together with air mass back trajectories and Moderate Resolution Imaging Spectroradiometer fire count data reveal that carbonaceous aerosols in winter/fall are significantly influenced by atmospheric aging (downwind transport of crop residue burning/wood combustion emissions in the northern IGP), while local sources (wheat residue combustion/vehicular emissions) dominate in spring/summer. Given the large temporal and seasonal variability in sources and emission strength of TC over the IGP, 14 C‐based constraints are, thus, crucial for reducing their uncertainties in carbonaceous aerosol budgets in climate models. Key Points: Year‐round 14 C‐based source apportionment of total carbon (TC) in the Indo‐Gangetic Plain (IGP) 14 C‐based isotopic analyses reveal that biomass burning emissions are a major source (77 ± 7%) of TC in the IGP The fossil contribution to carbonaceous aerosols in IGP is larger in summer than in winter/fall/spring